Analisis Kebijakan Publik terhadap Penyaluran Bantuan Program Indonesia Pintar (PIP) di Kota Bandar Lampung - Abdul Halim; Ratna Wulandari; Nadia Sabila; Eka Dea Pramudita; Dewi Rahayu; Bagus Permana; Adelia Novita Sari; Ferdiansyah, Ferdiansyah; Adinda Armilia Putri; Serly Pramudita (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
Based on Presidential Instruction Number 7 of 2014 concerning the implementation of the Family Welfare Savings Program, the Smart Indonesia Program, and the Healthy Indonesia Program as part of efforts to build productive families, this research aims to evaluate the implementation of the Smart Indonesia Program policy at all levels of elementary and junior high schools in Bandar Lampung City. This study uses a qualitative descriptive approach. The results of the study show that the implementation of the Smart Indonesia Program policy, particularly in the aspect of communication in the form of socialization between the Education Office and the schools, has been quite effective. However, there are still communication obstacles, namely that some parents have not understood the benefits and procedures for applying for the aid. From the perspective of resources, both the workforce and supporting facilities at the Education Office are considered adequate. In terms of disposition, the implementation of the duties and roles of the office and schools in this program has been carried out well. to the recipients of aid in Bandar Lampung City. Nevertheless, the school's supervision of students' use of aid funds is still less than optimal, as the school does not know exactly how those funds are used. Meanwhile, from a bureaucratic structure perspective, the implementation of the Smart Indonesia Program policy has been carried out, but schools still face challenges in identifying students who truly need this program.